If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 7h = -7 Solving 7h = -7 Solving for variable 'h'. Move all terms containing h to the left, all other terms to the right. Divide each side by '7'. h = -1 Simplifying h = -1
| 2/3-5/9= | | 5x+(-2)=-10 | | 15x+4-9=-32 | | 5x+1(-2)=-10 | | -3m+13-9(m-3)=6m-(5m-4)-8m+6 | | 2(4w)+2(w)=420 | | 15m+4-9x=-32 | | 3(4x+2)=2(6x-3) | | 5+3X-8=21 | | 3/7z=-26 | | 5x^2-42=-11x | | x^5+3x^4-x-3=0 | | 2(x+6)(x+6)=0 | | x/2+y/5=-3 | | 7x+37=4x | | 17=4N-15 | | x^2+34+6x+4+10x+10=180 | | -2+x-9= | | 9x+54=5x | | 24yds= | | 3y+42=9x+54 | | a/5-4=a/3+6 | | (2x+5)/(3x-5)=0 | | f(x)=-4x^2+3x+9 | | 10x-3=24+9x | | 2x+5/3x-5=0 | | 24p^3q+52p^2q^2+20pq^3=0 | | 5x-19=4x+4 | | 43-1n+16=44 | | (24a^3c^4)/2 | | 15=12+M/7 | | -9x^2-2x-9=0 |